2015
DOI: 10.1053/j.ajkd.2015.02.339
|View full text |Cite
|
Sign up to set email alerts
|

Longer-term Outcomes of Darbepoetin Alfa Versus Epoetin Alfa in Patients With ESRD Initiating Hemodialysis: A Quasi-experimental Cohort Study

Abstract: Background Adequately-powered studies directly comparing hard clinical outcomes of darbepoetin alfa (DPO) versus epoetin alfa (EPO) in patients undergoing dialysis are lacking. Study Design Observational, registry-based, retrospective cohort study; we mimicked a cluster-randomized trial by comparing mortality and cardiovascular events in US patients initiating hemodialysis in facilities (almost) exclusively using DPO versus EPO. Setting & Participants Non-chain US hemodialysis facilities; each facility swi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 27 publications
3
15
2
Order By: Relevance
“…Specifically, we used administrative data to mimic a cluster-randomized design, with clustering based on facility by assigning facilities and their incident hemodialysis patients to a treatment arm based on the predominant practice pattern of their facility. We have recently applied this design in a comparative safety study among erythropoiesis-stimulating agents [8].…”
Section: Study Rationalementioning
confidence: 99%
“…Specifically, we used administrative data to mimic a cluster-randomized design, with clustering based on facility by assigning facilities and their incident hemodialysis patients to a treatment arm based on the predominant practice pattern of their facility. We have recently applied this design in a comparative safety study among erythropoiesis-stimulating agents [8].…”
Section: Study Rationalementioning
confidence: 99%
“…To wit, we observed that nearly 70% of European facilities use more than 1 ESA type, and nearly 30% use 3 or more. Comparative studies of established ESA products have generally been unable to detect substantial differences in efficacy or safety outcomes [11][12][13]. The decision to use 1 ESA over another can thus be summarized by several other factors: chiefly cost, availability, and preferences for dosing fre- quency [14].…”
Section: Discussionmentioning
confidence: 99%
“…We have recently used this design in two comparative safety studies of erythropoiesis-stimulating agents and of ferumoxytol, and the following resembles the methods described therein. (8, 9) This approach is particularly attractive for the intermittent nature of iron treatment, where iron storage parameters and (temporary and sometimes relative) contraindications will lead to potentially strong, and partly unobserved, time-dependent confounding that may be difficult to accommodate using traditional or novel (marginal-structural models) methods for time-dependent exposures.…”
Section: Methodsmentioning
confidence: 99%